Cancer stem cells and mesenchymal stem cells in the hypoxic tumor niche: Two different targets for one only drug. Issue 3 (March 2015) - Bonafè, Francesca; Guarnieri, Carlo; Muscari, Claudio
Abstract Putative cancer stem cells (CSCs) reside in a hypoxic microenvironment where mesenchymal stem cells (MSCs) are also present. In this niche MSCs seem to promote the generation of CSCs and sustain tumor progression. Therefore, it may assume clinical relevance to produce a drug which kills not only CSCs but also MSCs. We hypothesized that bifunctional nanoparticles, loaded with a HIF-1α inhibitor and conjugated with an aptamer targeting a common receptor of CSCs and MSCs, may fulfill this strategy. The nanoparticle should ensure that: (1) the conveyed drug is less susceptible to degradation, (2) the common receptor of CSCs and MSCs is recognized by a superselective aptamer, and (3) receptor-mediated internalization is the main process to enter target cells. Small RNA or DNA aptamers represent an advantage over antibodies because do not cause immune reactions, are better internalized into the target cell, are more resistant to degradation, their cost of production are lower, and the purity of the oligonucleotide ligand is extremely elevated. Concerning the drugs to be delivered, we suggest to employ those exerting an anti-HIF-1α activity because they should be harmful for hypoxic CSCs and MCSs in their tumor niche but provide very limited toxicity, or even none, to well-oxygenated normal cells. Corresponding experimental approaches to perform pre-clinical studies and verify this hypothesis are also addressed.